2019
DOI: 10.1523/jneurosci.2817-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin-Sensitive Sodium Channels Mediate Action Potential Firing and Excitability in Menthol-Sensitive Vglut3-Lineage Sensory Neurons

Abstract: Small-diameter vesicular glutamate transporter 3-lineage (Vglut3 lineage) dorsal root ganglion (DRG) neurons play an important role in mechanosensation and thermal hypersensitivity; however, little is known about their intrinsic electrical properties. We therefore set out to investigate mechanisms of excitability within this population. Calcium microfluorimetry analysis of male and female mouse DRG neurons demonstrated that the cooling compound menthol selectively activates a subset of Vglut3 lineage neurons. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…S1d, the response to cold or menthol did not differ in cultured sensory neurons exposed to morphine or in neurons isolated from morphine-treated mice, relative to control. In accordance with previous published results [12,21,25,26], we found that cold sensitive DRG neurons were a rare subset of small diameter neurons (< 20 µm in diameter). In control mice, 3.06% of total neurons (37/1200) responded to cold and 3.31% (37/1138) to menthol (100 µM).…”
Section: Chronic Morphine Reduces Both Cold and Menthol-evoked Desenssupporting
confidence: 93%
“…S1d, the response to cold or menthol did not differ in cultured sensory neurons exposed to morphine or in neurons isolated from morphine-treated mice, relative to control. In accordance with previous published results [12,21,25,26], we found that cold sensitive DRG neurons were a rare subset of small diameter neurons (< 20 µm in diameter). In control mice, 3.06% of total neurons (37/1200) responded to cold and 3.31% (37/1138) to menthol (100 µM).…”
Section: Chronic Morphine Reduces Both Cold and Menthol-evoked Desenssupporting
confidence: 93%
“…S1d, the response to cold or menthol did not differ in cultured sensory neurons exposed to morphine or in neurons isolated from morphine-treated mice, relative to control. In accordance with previous published results [12,21,25,26], we found that cold sensitive DRG neurons were a rare subset of small diameter neurons (< 20 μm in diameter). In control mice, 3.06% of total neurons (37/1200) responded to cold and 3.31% (37/1138) to menthol (100 μM).…”
Section: Chronic Morphine Reduces Both Cold and Menthol-evoked Desenssupporting
confidence: 93%
“…RNAscope analysis was performed using the ACDbio RNAscope kit for nonfixed tissue (ACD #320851) based on ref. 71 . In short, DRG extracted from adult mice were fixed for 15 min in 4% PFA, washed in PBS, and allowed to equilibrate in 30% sucrose for 2 h before embedding in OCT (Tissue Tek; Sakura Finetek).…”
Section: Methodsmentioning
confidence: 99%